Community participation in cleanliness education to maintain the quality of river ecosystems in Indonesia - Moshka Dewi Azzahra (Journal of Character and Environment, 2026)
Background: The degradation of river ecosystem quality in Indonesia remains a complex environmental issue caused by domestic waste, urbanization, industrial activities, and ineffective community-based waste management. Technical approaches alone have not been fully effective without behavioral changes supported by environmental education and community participation. This study aims to analyze community participation in river cleanliness education, identify supporting and inhibiting factors, and evaluate the role of environmental education in sustaining river ecosystems in Indonesia. Methods: This study employed a Systematic Literature Review (SLR) method using the PRISMA 2020 approach. Literature was collected from Google Scholar and ScienceDirect using the keywords “public participation,” “environmental education,” “river ecosystem,” and “Indonesia.” From 305 identified articles, 15 articles published between 2015 and 2025 met the inclusion criteria and were analyzed using descriptive and thematic analysis approaches. Findings: The results indicate that community participation remains predominantly focused on operational activities, such as river clean-up programs, waste management, and environmental campaigns, while involvement in planning and decision-making remains limited. Participatory environmental education through Participatory Action Research (PAR), citizen science, and community collaboration contributes to increasing ecological awareness, behavioral change, and collective action. Supporting factors include contextual education, local leadership, institutional support, and experiential learning, while barriers include limited information access, insufficient community capacity, weak institutional support, and top-down governance approaches. Conclusion: River ecosystem sustainability is strongly influenced by the quality of community participation and the effectiveness of environmental education programs. Collaborative and participatory education can encourage sustainable environmental practices and strengthen community-based river management. Novelty/Originality of this article: This study provides an integrative socio-ecological synthesis of the relationship between environmental education, community participation, and river ecosystem sustainability. It also develops an evidence-based conceptual framework for participatory river management policies in Indonesia.